Obtenção e caracterização de (1→6)-β-D-glucana (Lasiodiplodana) carboximetilada com diferentes graus de substituição - Theis, Thaís Vanessa (2018)
The diverse possibilities of technological and biological applications of β-glucans have aroused the interest of the chemical, pharmaceutical and food industries. Some of them are notable for their anticoagulant, antithrombotic, antiinflammatory and anti-inflammatory activities, while others are effective in the treatment of viral and infectious diseases. The biological potential of β-glucans is directly associated with the primary structure of the macromolecule, and therefore structural chemical modifications may potentiate or confer functionalities to the biomacromolecule. In this context, the present study proposed the chemical derivatization of (1→6)-β-D-glucan (lasiodiplodan) by carboxymethylation and the evaluating of the influence of diferent concentrations of the derivatizing agent on the degree of substitution. The derivatized macromolecules were characterized by Fourier Transform-Infrared (FT-IR) spectroscopy, thermal analysis (TG/DTA), X-ray diffractometry (XRD), scanning electron microscopy (SEM), antioxidant activity and water solubility. Carboxymethyl derivatives with different degrees of substitution (DS 0.32; 0.47; 0.51; 0.58 and 0.68) were obtained and there seems to be a correlation between concentration of the derivatizing agent and the DS. The (FT-IR) spectroscopy analysis indicated the insertion of carboxymethyl groups in the macromolecule structure by the appearance of bands of strong intensity at 1600 cm-1 and the band at 1421 cm-1 resulting from the asymmetric and symmetrical stretching vibrations of the COO- group of carboxymethyl. Thermal analysis (TG/DTA) showed that native lasiodiplodan (LN) and carboxymethylated derivatives (LC) presented high termal stability (200-210 ºC). The diffractive profile of the LN and LC samples demonstrated that the samples have a predominantly amorphous nature. SEM analysis revealed that carboxymethylation promoted morphological changes on the surface of the biopolymer, arising porosity and alveolar structures along the surface. The introduction of carboxymethyl groups in the lasiodiplodan potentiated the hydroxyl radical removal ability, and there appears to be a concentration-dependent correlation. Carboxymethylation also promoted increased solubility of lasiodiplodan in water and derivatives with solubility between 45.5 a 67.9 mg/100mL were obtained.